Microsponge: A Novel Drug Delivery System - Dumbre, A. K.; Banerjee, S. K.; Gadhave, M V; Gaikwad, D D (Asian Journal of Pharmaceutical Research and Development, 2014)
Conventional topical formulations are intended to work on the surface of the skin. Normally, upon application such formulations release their active ingredients and producing a highly concentrated layer of active ingredient that is quickly absorbed. Microsponge delivery System was originally developed for topical delivery of drugs can also be used for controlled oral delivery of drugs using water soluble and bioerodible polymers. It holds a promising future in various pharmaceutical applications in the coming years like enhanced product performance and elegancy, extended release, reduced irritation, improved thermal, physical, and chemical stability of product. Microsponges are polymeric delivery systems composed of porous microspheres. They are tiny sponge-like spherical particles with a large porous surface. Moreover, they may enhance stability, reduce side effects and modify drug release favorably. Microsponge technology has many favorable characteristics, which make it a versatile drug delivery vehicle. The outer surface is typically porous, allowing a sustained flow of substances out of the sphere. Microsponges are porous, polymeric microspheres that are used mostly for topical use and have recently been used for oral administration. Microsponges are designed to deliver pharmaceutical active ingredient efficiently at the minimum dose and also to enhance stability, reduce side effects, and modify drug release.